Play and Hysteria in Theatre Silviu Purcarete’s Danaids - Titieni, Adriana (European Scientific Journal, ESJ, 2017)
The following article proposes a case study of Eschil’s character, Hypermnestra from The Danaids trilogy. In the artistic process, all performances strike high notes of human sensitivity that only an unbalanced psychic can reach. The psychosis and the hysteria may constitute a model for the exaltation of the theatrical performance, without altering art’s mimetic character.